DESACYLATED GHRELIN AND LEPTIN IN THE CORD BLOOD OF SMALL-FOR-GESTATIONAL-AGE NEWBORNS WITH INTRAUTERINE GROWTH RESTRICTION - Bucur-Grosu, M.L. (Acta Endocrinol (Buchar), 2019)
CONTEXT: Ghrelin, in both its acylated and desacylated forms, and leptin can modulate fetal energy balance and development. OBJECTIVE: The aim of our study is to assess desacylated ghrelin (DAG) and leptin values and influence on intrauterine and postnatal growth in infants with intrauterine growth restriction. DESIGN, SUBJECTS AND METHODS: We performed a prospective study on 39 infants recruited over five months, 20 appropriate - for - gestational - age (AGA) infants and 19 small-for-gestational-age (SGA) infants, in which we measured DAG and leptin in the umbilical cord blood and we compared their respective values between the two groups, along with auxological parameters at birth and at 10 months of postnatal age. RESULTS: Our results show that both DAG and leptin have lower values in SGA infants and correlate with most of the anthropometrical parameters at birth. Both hormones correlate with weight at 10 months in SGA infants, but this correlation lacks in AGA infants. Whereas DAG in the cord blood can be considered a predictor for weight at 10 months (β=0.207, p=0.001), the same cannot be stated about leptin (β=0.078, p=0.195). CONCLUSION: DAG and leptin are involved in both intrauterine and postnatal development, but the extent of their role is still to be determined.